Multi‐Omics Analysis Reveals Impacts of LincRNA Deletion on Yeast Protein Synthesis - Ling Qin; Yuyang Pan; Songlyu Xue; Zhibo Yan; Chufan Xiao; Xiufang Liu; Dan Yuan; Jin Hou; Mingtao Huang (Advanced Science)
Abstract Non‐coding RNAs (ncRNAs) are widespread across various genomic regions and play a crucial role in modulating gene expression and cellular functions, thereby increasing biological complexity. However, the relationship between ncRNAs and the production of heterologous recombinant proteins (HRPs) remains elusive. Here, a yeast library is constructed by deleting long intergenic ncRNAs (lincRNAs), and 21 lincRNAs that affect α‐amylase secretion are identified. Targeted deletions of SUT067, SUT433, and CUT782 are found to be particularly effective. Transcriptomic and metabolomic analyses of the top three strains indicate improvements in energy metabolism and cytoplasmic translation, which enhances ATP supply and protein synthesis. Moreover, a yeast strain, derived from the SUT433 deletion, that can secrete ≈4.1 g L⁻1 of α‐amylase in fed‐batch cultivation through the modification of multiple targets, is engineered. This study highlights the significant potential of lincRNAs in modulating cellular metabolism, providing deep insights and strategies for the development of more efficient protein‐producing cell factories.